Increased risk of antiphospholipid syndrome in patients with psoriasis: a retrospective cohort study - Wang, Qian; Cui, Ran; Du, Yu; Wang, Yu-Hsun; Wei, James Cheng-Chung; Dai, Sheng-Ming (Frontiers in Immunology, 2025)
ObjectivesPsoriasis is associated with systemic inflammation and immune dysregulation, raising concerns about its potential link to antiphospholipid syndrome (APS). However, evidence on the risk of APS in psoriasis patients remains limited.Materials and methodsThis retrospective cohort study utilized data from the TriNetX US Collaborative Networks (2002–2022). Propensity score matching (1:1) was performed to balance demographic variables, comorbidities, and medication use between 288,678 psoriasis and non-psoriasis patients. The univariate Cox proportional hazard model and subgroup analyses were used to estimate the hazard ratio for APS. The Kaplan-Meier method was used to plot the cumulative incidence curves.ResultsAfter matching, each cohort included 288,678 patients. Psoriasis patients exhibited significantly higher APS incidence (1,349 cases vs. 673 in controls; HR: 1.71, 95% CI: 1.56–1.88). Psoriatic arthritis (PsA) further amplified risk (HR: 1.91, 95% CI: 1.58–2.31). Subgroup analyses identified elevated APS susceptibility in older adults, females, Black/African American individuals, and those with chronic comorbidities.ConclusionsPsoriasis and psoriatic arthritis are significant risk factors for APS, highlighting the need for targeted screening and management strategies in these populations.